Nonlinear optical spectroscopy of epitaxial magnetic garnet films: Магнетизм - Pavlov, V. V.; Pisarev, R. V.; Fiebig, M.; Fröhlich, D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
Second and third harmonic optical spectra are studied in epitaxial magnetic thin films in the spectral ranges 1.7-3.2 eV and 2.4-4.2 eV, respectively. No significant increase of the intensity of the nonlinear spectra is found above the bandgap near 3.2 eV, where the linear absorption increases by two orders of magnitude. Large magnetic contributions to the second harmonic spectra and magnetic contrast as high as 100% are observed at selected photon energies. Contrary to that, no magnetic contribution to the third harmonic spectra is found.